A single-bit sampling demodulator for biomedical implants. Issue 8 (August 2015) - Kim, Duho; Ko, Minsu; Ng, David; Choi, Woo-Young
Abstract A phase-shift keying (PSK) demodulator is demonstrated for the target application of low power and high data rate inductive links. The demodulator based on the single-bit sampling demodulation scheme is capable of operating in binary, quadrature, 8-, and 16-PSK mode. The prototype chip realized in 0.18-µm CMOS process can demodulate up to 1.25 MSymbol/s at 5-MHz carrier frequency. It occupies 240×310 µm2 and consumes 140 µA from 1.2 V.